Forgiving the dead man walking - Morris, Debbie, 1964-; Lewis, Gregg, 1951- (Grand Rapids, Mich. : Zondervan Pub. House, 1998)
Robert Willie, the death-row prisoner in Dead Man Walking, was convicted of raping a woman who tells her story here.
Keywords: Morris, Debbie, -- 1964-; Victims of crimes -- Louisiana -- Madisonville -- Psychology; Murder -- Louisiana -- Madisonville -- Case studies; Serial murderers -- Louisiana -- Madisonville -- Case studies